Can an Anchored Cage be Substituted for an Anterior Cervical Plate and Screw for Single-Level Anterior Cervical Fusion Surgery?: Prediction of Poor Candidates Through a Review of Early Clinical and Radiologic Outcomes. Issue 9 (November 2017) - Seo, Dong Kwang; Kim, Moon Kyu; Choi, Soo Jung; Sohn, Jun Young; Kim, Young Ki; Jeong, Eui Kyun; Ha, Jung-Ki; Kim, Chung Hwan; Park, Jin Hoon
Abstract : Study Design: This is a case series of device failure patients. Objective: To identify poor candidates for anterior cervical discectomy and fusion (ACDF) using an anchored cage. Summary of Background Data: An anchored cage has been used as an alternative implant for ACDF surgery because of ease of use, relatively acceptable fusion rate, and lower risk of plate-related complications, including dysphagia. Materials and Methods: We retrospectively reviewed the outcomes of 36 patients who underwent ACDF using an anchored cage between January 2012 and December 2013. The initial diagnoses included 8 traumatic soft disk herniations without posterior ligamentous complex injury, 25 degenerative soft disk herniations, 1 degenerative foraminal stenosis, 1 traumatic soft disk herniation after reducing a unilaterally dislocated facet joint, and 1 subluxation of a previously implanted cervical artificial disk. We encountered 5 cases with poor outcomes and performed 3 revisions on the index level. We reviewed the clinical and radiologic data for 31 patients with reasonable outcomes and reviewed the failed 5 cases separately. Results: Among the 31 patients with reasonable outcomes, all the clinical parameters improved. For the radiologic outcomes, 10 cases of cage subsidence occurred and no patient experienced instability. Among the 5 patients with poor outcomes, 1 patient had traumatic soft disk herniation and a reduced unilaterally dislocated facet joint, 1 patient had subluxation of a previously implanted cervical artificial disk, and 3 patients had degenerative soft disk herniation and poor bone quality. Although 3 patients required revision surgeries, 2 patients showed only radiologic failures without revision. Conclusions: We analyzed the short-term outcomes of ACDF using an anchored cage and observed 5 patients with poor outcomes among 36 patients. We recommend the use of a single anchored cage for patients with definite evidence of posterior column stability and healthy bone. Level of Evidence: Level 3.